Proceedings of the conference Contemporary Mathematics in Kielce 2020, February 24-27 2021 (De Gruyter, 2021)
The main purpose of the conference is to stimulate the exchange of new ideas in algebra, topology and geometry, and to celebrate 50 years of the Jan Kochanowski University.